Concise synthesis of 3-C-glycosyl isocoumarins and 2-glycosyl-4H-chromen-4-ones - Liu, Deng-Yin; Ruan, Yu-Jun; Wang, Xiao-Li; Hu, Xin-Yue; Wang, Peng-Fei; Wen, Miao-Miao; Zhang, Cong-Zhen; Xiao, Yu-He; Liu, Xu-Ge (Chemical communications (Cambridge, England), 2024)
A new Ru-catalyzed C-H activation/cyclization reaction for the synthesis of 3-C-glycosyl isocoumarins and 2-glycosyl-4H-chromen-4-ones with carbonyl sulfoxonium ylide glycogen are reported. In this catalytic system, benzoic acid and its derivatives react with carbonyl sulfoxonium ylide glycogen to yield isocoumarin C-glycosides, while 2-hydroxybenzaldehyde substrates react to produce chromone C-glycosides. These reactions were characterized by mild reaction conditions, broad substrate scope, high functional-group compatibility, and high stereoselectivity to yield several high-value isocoumarins and chromone skeleton-containing C-glycosides. The methods were successfully implemented in the context of large-scale reactions and the late-stage modification of complex natural products.